2022
DOI: 10.1111/jan.15520
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intrapartum health outcomes among Black birthing persons: A discursive paper

Abstract: Aim: To examine factors that influence intrapartum health outcomes among Black childbearing persons, including cisgender women, transmasculine and gender-diverse birthing persons. Background: Black childbearing persons are three to four times (243%) more likely to die while giving birth than any other racial/ethnic group. Black birthing persons are not just dying from complications but also from inequitable care from healthcare providers compared to their white counterparts. Design: Discursive paper. Method: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…This finding is surprising given the ample literature suggesting that there are differences in quality of care provided to Black individuals. 15–19 However, we note that this finding, which exists in the setting of a randomized trial conducted at academic medical centers, may not reflect findings in the general community and may be nonsignificant because of type II error. In addition, we note that greater perceived pain was associated with lower Labor Agentry Scale scores, and there is ample literature suggesting that Black birthing individuals experience less optimal control of their intrapartum and postpartum pain.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This finding is surprising given the ample literature suggesting that there are differences in quality of care provided to Black individuals. 15–19 However, we note that this finding, which exists in the setting of a randomized trial conducted at academic medical centers, may not reflect findings in the general community and may be nonsignificant because of type II error. In addition, we note that greater perceived pain was associated with lower Labor Agentry Scale scores, and there is ample literature suggesting that Black birthing individuals experience less optimal control of their intrapartum and postpartum pain.…”
Section: Discussionmentioning
confidence: 74%
“…Patient experiences are multifaceted, and although other studies have reported findings generally similar to ours, they also have provided additional insight with regard to the suboptimal experiences for individuals from communities with historical disadvantage such as people of color and of low economic status. [16][17][18][19]28,29 This analysis included a large diverse sample of nulliparous people at low risk. The findings represent perceived control during childbirth based on Labor Agentry Scale scores among people receiving care in the United States, which is important considering that many similar studies examined international populations, who may differ in important ways from a U.S. population with regard to attitudes, beliefs, and preferences during the birth experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the implicit bias that providers experience has particularly costly implications. Even with the purest of intentions, implicit bias can influence providers to discredit pain, dismiss symptoms, and ignore best practices, often silencing voices of Black birthing women (Gillette‐Pierce et al, 2022). Provider bias results in the blatant ignorance of urgent maternal warning signs in Black women.…”
Section: Implicit Bias In Reproductive Healthcarementioning
confidence: 99%
“…Evidence‐based literature supports that social determinants of health such as low socioeconomic status, low levels of educational attainment and limited access to healthcare as contributing factors to health disparities. However, for Black birthing women, social determinants of health are not always a causative factor for these poor health outcomes (Gillette‐Pierce et al, 2022). Although maternal health status is multifactorial, racism is an irrefutably significant contributor to the disparities in maternal morbidity and mortality rates.…”
mentioning
confidence: 99%